Warriors. Graystripe's adventure 3, Warrior's return - Hunter, Erin; Jolley, Dan (Hunter, Erin. Warriors (Graphic novel), 2008)
Describes the adventures of Graystripe, a former leader of ThunderClan, as he struggles between staying with his adopted Twoleg family and embarking on a quest to find his lost feline companions.